Genetic variability in Rampur Bushair sheep breed using microsatellites markers - PANDEY, A K; SHARMA, REKHA; SINGH, YATENDER; MISHRA, B P (The Indian Journal of Animal Sciences, 2011)
Genetic variability at 20 Inicrosatellites was analysed on the basis of individual genotypes in Rampur Bushair sheep. The observed number of alleles varied from 2 to 9 with an overall mean of 6.0±1.91. The observed number of alleles across all the loci were more than the effective number of alleles (3.47±1.29). The average observed heterozygosity was O.515±0.18 which was less than the expected (O.675±0.14). The average f estimate (FIS ) was O.227±O.05 indicating heterozygote deficiency in the population. Population was in mutation drift equilibrium. Rampur Bushair sheep had substantial genetic variation based on its gene diversity and average number of alleles per locus.